Breeding biology and nesting success of the endemic Black-cheeked Gnateater (Conopophaga melanops). (2nd September 2019) - Studer, Anita; de Sousa, Marcelo Cardoso; Barcena-Goyena, Begoña
ABSTRACT: Life history traits are essential for better understanding avian populations. In some cases, timing of the breeding season depends on external environmental factors such as photoperiod, rainfall, food availability and temperature. Here we describe the life history traits of a northeastern population of Black-cheeked Gnateater and we aim to understand the factors behind fluctuations on life-history traits. Breeding was quite seasonal, with the core of the breeding season right before the beginning of heavy rains. Highest numbers of active nests occurred in April and nesting activity was lowest from July to September, a period matching the shortest and coldest months of the year. Daily survival rate (DSR) for the whole nesting cycle was 0.883 d −1, giving a Mayfield nest success of 12.9%. Our data suggest that this population uses environmental factors as cues to modulate breeding activity.